Qui sont nos ennemis? Qui sont nos amis? La presse pakistanaise et ses perceptions des attitudes et politiques de quatre grandes puissance 1958-1965. - Hassan, Ashraful; Burton, Bruce; Soderlund, W.C. (Études internationales, 1982)
Utilizing content analysis methodology, this paper studies Pakistani press perceptions of external sources of threat and support covering the Period 1958-1965.From the literature on Pakistani foreign policy, seven specific hypotheses are extractedfor testing:1 - during the period 1958-1965, India was perceived to be the major threat toPakistan ;2 - the perception of India as the major threat increased sharply from 1962 onwards;3 - in 1959 China was perceived to be a greater threat to Pakistan than India was;4 - the Soviet Union was perceived to be the major threat in 1958, a significant butsecondary threat in 1959, the main threat again in 1960, and an insignificantthreat from 1961 onwards;5 - at no time during the period 1958-1965 was the United States perceived to be athreat to Pakistan;6 - the respective policies of China, the US.S.R., and the U.S. towards South Asia ingeneral and on the Kashmir issue in particular, played a major part in determiningPakistan's attitudes toward these states;7 - U.S. arms aid to India in 1962 resulted in a major Pakistani disillusionment withthe United States and this was accompanied by more positive Pakistani viewstoward the US.S.R. and China.Our data drawn from front page news stores and editorials appearing in a sample of the Pakistani newspaper Dawn, confirm in general terms hypotheses 1, 2, 5, 6, and 7, but fall to confirm hypotheses 3 and 4.Overall, the data point to the significance of the Sino-Indian border war in the fall of 1962 as a crucial turning point in Pakistan 's foreign policy alignments. Specifically, we see evidence of a turning away from the United States, combined with a movement toward China. Attitudes toward the Soviet Union were ambivalent.